2013
DOI: 10.1007/s00404-013-2900-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium supplementation to prevent high blood pressure in pregnancy: a randomised placebo control trial

Abstract: Magnesium supplementation prevented an increase in diastolic blood pressure during the last weeks of pregnancy. The relation between diastolic blood pressure and urinary excretion of magnesium suggests that magnesium is involved in the regulation of blood pressure and that the increase in diastolic blood pressure in pregnancy could be due to a lack of magnesium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
0
13
0
7
Order By: Relevance
“…Доказано, что пероральный прием магния оротата эффективен для предотвращения повышенного АД во время беременности [37].…”
Section: влияние препаратов магния на репродуктивную функцию женщинunclassified
“…Доказано, что пероральный прием магния оротата эффективен для предотвращения повышенного АД во время беременности [37].…”
Section: влияние препаратов магния на репродуктивную функцию женщинunclassified
“…However, as only two of the 10 RCTs were considered to be of higher quality, the authors concluded that there is insufficient evidence as to whether oral magnesium supplementation in pregnancy is beneficial to mother or fetus [23]. Additionally, the effect of magnesium supplementation in the prevention of prematurity has had conflicting results, perhaps partly due to different the different forms of magnesium assessed in those trials [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Он является дезагрегантом и умеренным антикоагулян-том [16,17]. Во время беременности изменяется регуля-ция гомеостаза магния в организме, усиливается его экскреция с мочой, что также может приводить к повы-шению артериального давления [1,18,19]. Значительное количество исследований подтверждает снижение уров-ня магния в плазме крови и эритроцитах у женщин с пре-эклампсией в сравнении с группой контроля [1].…”
unclassified
“…Учитывая вышесказанное, отечественными и зарубеж-ными авторами проведено множество исследований и доказано снижение частоты развития и тяжести преэ-клампсии на фоне комплексной профилактики с исполь-зованием препаратов магния [17,18,21].…”
unclassified